Control of Fractional-Order Unified Chaotic Systems Subject to External Disturbances Using Twisting Algorithm with Fractional Integral Sliding Surface - Khamsuwan, Pitcha; Sangpet, Teerawat; Kuntanapreeda, Suwat (International journal of applied and computational mathematics, 2019)
This paper focuses on output feedback control of fractional-order unified chaotic systems subject to external disturbances. The output feedback controller is a combination of a high-order sliding mode controller and an observer. The controller based on a twisting algorithm makes use of a fractional integral sliding surface. The observer is a nonlinear state observer. Stability conditions for the output feedback control system are formulated as a linear matrix inequality problem. Numerical studies are given, showing the effectiveness of the method.